2010
DOI: 10.1083/jcb.201003081
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-3 and Notch cooperate in regulating adult myogenesis

Abstract: Syndecan-3 is required for Notch processing by ADAM17/TACe and therefore regulates proliferation and viability of muscle satellite cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
110
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 59 publications
3
110
0
1
Order By: Relevance
“…A recent report demonstrated that GDNF and ARTN also interact with SYNDECAN-3, a transmembrane heparin sulfate proteoglycan with subsequent activation of Src kinase (50). SYNDECAN-3 is expressed in myogenic stem cells and cooperates with Notch to promote cell cycle progression and self-renewal and inhibit terminal differentiation (51). This alternate receptor for ARTN may be highly relevant in the context that the MDA-MB-231 cell line used herein does not express RET (52), and therefore, the observed effects of ARTN on the CSC-like phenotype in these cells are RET independent.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report demonstrated that GDNF and ARTN also interact with SYNDECAN-3, a transmembrane heparin sulfate proteoglycan with subsequent activation of Src kinase (50). SYNDECAN-3 is expressed in myogenic stem cells and cooperates with Notch to promote cell cycle progression and self-renewal and inhibit terminal differentiation (51). This alternate receptor for ARTN may be highly relevant in the context that the MDA-MB-231 cell line used herein does not express RET (52), and therefore, the observed effects of ARTN on the CSC-like phenotype in these cells are RET independent.…”
Section: Discussionmentioning
confidence: 99%
“…Following muscle injury, quiescent satellite cells present in basal lamina get activated, which proliferate and finally fuse with injured myofibers leading to regeneration and repair (11,18). Notch signaling is critical not only for the activation of satellite cells but also for their terminal differentiation into myofibers and to maintaining the satellite cell pool (14,16,31,32,52,54,56,60). We found that the depletion of TRAF6 specifically in differentiated myofibers significantly increases the number of satellite cells upon injury, leading to rapid and faster restoration of muscle architecture ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Notch signaling is a prerequisite for the expansion of postnatal satellite cells and to prevent the premature differentiation of myogenic precursors in injured myofibers (14,16,31,32,52,54,56,60). Age-associated decline in satellite cell proliferative capacity is attributed, at least in part, to the insufficient upregulation of Notch ligand DLL and hence reduced activation of Notch leading to impaired muscle regeneration (14).…”
mentioning
confidence: 99%
“…For example, matrix heparan sulfate proteoglycans Syndecan 3 and Syndecan 4 regulate the self-renewal, proliferation, and differentiation of satellite cells through modulating Notch signaling (11,13,48). Loss of Syndecan 3 leads to reduced expression of Notch target genes due to defective ADAM17/TACE-mediated S2 cleavage and ␥-secretase-mediated S3 cleavage in Notch processing (37). More recently, it has been shown that Dll1 expressed by neural crest progenitors migrating en route through embryonic somites transiently activates Notch signaling in myogenic progenitors and promotes myogenic differentiation (40).…”
mentioning
confidence: 99%